2022
DOI: 10.3389/fpsyg.2022.898203
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perceived Risk of COVID-19, Psychological Distress, and Internet Addiction in College Students: An Application of Stress Process Model

Abstract: The closed-off management of the university during coronavirus disease 2019 (COVID-19) may be associated with an elevated odds of psychological and behavioral issues among college students. We aimed to use the stress-process model to explore the potential mechanisms for this phenomenon. A total of 924 college students were recruited via posters, peer referrals, and class attendance. Among them, 82 (9%) were probable depression, 190 (20.8%) were probable anxiety, and 69 (7.5%) were internet addiction. Parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…62 Internet addiction made college students insufficient personal communication with peers, thereby leading to mental health problem. 56 Interestingly, the significance of sex and siblings in the univariate analyses disappeared in the multivariate analyses, suggesting that the associations of sex and siblings with mental health are dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Internet addiction made college students insufficient personal communication with peers, thereby leading to mental health problem. 56 Interestingly, the significance of sex and siblings in the univariate analyses disappeared in the multivariate analyses, suggesting that the associations of sex and siblings with mental health are dependent.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Negative coping style associated with psychological distress in Chinese college students. 56 A recent study conducted in a large university of the Mid-Atlantic region in the United States showed that extraversion and avoidance coping style moderated the effect of COVID-19 stressful life events on mental health. 57 Moreover, a positive correlation was observed between positive coping style and less psychological distress in Indian population during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…A two-phase longitudinal study showed that during the COVID-19 pandemic, Chinese children with activeavoidance coping style had a low level of anxiety and depression 55 . Negative coping style associated with psychological distress in Chinese college students 56 . A recent study conducted in a large university of the Mid-Atlantic region in the United States showed that extraversion and avoidance coping style moderated the effect of COVID-19 stressful life events on mental health 57 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the COVID-19 epidemic may still cause great bodily harm or even death [ 20 ]. In order to contain the spread of the epidemic, the Chinese government has implemented extremely strict prevention and control policies, such as: Closed all schools [ 21 ], confined students to their homes [ 22 ] or isolated college students from the outside world by confining them to their schools [ 23 ]. The virus was highly transmissible and contagious [ 24 ], causing “fear” [ 25 ] and negative emotions among Chinese college students [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in Nigeria noted that college students were at an increased risk of Internet addiction during the COVID-19 epidemic and found higher levels of Internet addiction among students in EKSU (public universities) or liberal arts colleges [ 46 ]. Several recent studies have shown that the COVID-19 perceived risk is positively associated with Internet addiction in different populations [ 4 , 23 , 27 , 48 ]. One study conducted in outbreak-controlled regions in China further revealed that the COVID-19 risk perception was significantly positively associated with Internet addiction among college students experiencing campus lockdown, and COVID-19 perceived risk could positively predict Internet addictive behavior [ 23 ].…”
Section: Introductionmentioning
confidence: 99%